Quiz (1 point)
- sum of (list x and xs) (list y and ys) and carry bit carry = list (sum of bit x bit y and bit carry) and (sum of xs ys and carry bit (carry on sum of bit x bit y and carry))
- sum of bit 0 bit 0 and bit 0 = 0
- carry on sum of bit 0 bit 0 and 0 = 0
- sum of (empty list) (empty list) and carry bit 0 = empty list
if sum of bit 0 bit 0 and bit 0 = 0, then list (sum of bit 0 bit 0 and bit 0) and (sum of (empty list) (empty list) and carry bit (carry on sum of bit 0 bit 0 and 0)) = list 0 and (sum of (empty list) (empty list) and carry bit (carry on sum of bit 0 bit 0 and 0))
if the following are true:
- a = b
- b = c
then a = c
if carry on sum of bit 0 bit 0 and 0 = 0, then sum of (empty list) (empty list) and carry bit (carry on sum of bit 0 bit 0 and 0) = sum of (empty list) (empty list) and carry bit 0
if sum of (empty list) (empty list) and carry bit (carry on sum of bit 0 bit 0 and 0) = sum of (empty list) (empty list) and carry bit 0, then list 0 and (sum of (empty list) (empty list) and carry bit (carry on sum of bit 0 bit 0 and 0)) = list 0 and (sum of (empty list) (empty list) and carry bit 0)
if the following are true:
- a = b
- b = c
then a = c
if sum of (empty list) (empty list) and carry bit 0 = empty list, then list 0 and (sum of (empty list) (empty list) and carry bit 0) = list 0 and (empty list)
if the following are true:
- a = b
- b = c
then a = c
Please write your proof in the table below. Each row should contain one claim. The last claim is the statement that you are trying to prove.